The making of Indian secularism : empire, law and Christianity, 1830-1960 - Chatterjee, Nandini, 1976- (Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"This book examines religion in India under British rule and the immediate postcolonial years, from an unusual angle, placing Indian Christians at the centre of the story. It addresses legal developments regarding religion and its practice during British imperial rule in India, and the political emergence of Indian Christians as a community in this context"--
Machine generated contents note: -- List of Illustrations -- Abbreviations -- Glossary -- Introduction -- Religion and Public Education: the Politics of Secularizing Knowledge -- Regulating Trust: Law and Policy of Religious Endowments in India -- Universality in Difference: the Emergence of Christian Personal Law in Colonial India -- Creating a Public Presence: the Missionary College of St. Stephens, Delhi -- Education for uplift: Christian Agricultural Colleges in India -- Authority and Conflict in the Indian Church -- Rethinking Christianity in India: Shaping the Religion in which they Believed -- Representing Christians: community interests vs. Christian Citizenship -- Conclusion The crime of Conversion and other Historical Curiosities -- Appendix: Christians per 10,000 of Population in India, 1881-1941 -- Bibliography.
Includes bibliographical references and index.
Keywords: Education, Higher -- India; Religious education -- India; Religion and state -- India; Christians -- India; Minorities -- India -- Political aspects; Minorities -- Legal status, laws, etc. -- India